Co3O4/Zn–Co–Mo Nanomaterials and Their Applications in Supercapacitors and Electrocatalysis Hydrogen Evolution Reaction. Issue 2 (1st February 2022) - Miao, Fengjuan; Shi, Jinxin; Tao, Bairui; Zang, Yu; Chu, Paul K.
Abstract : Mixed transition metal compounds with abundant more active sites are attractive to supercapacitors and electrochemical water splitting. In this work, the Co3 O4 /Zn–Co–Mo/NF composite is prepared by a hydrothermal method and thermal annealing. The Zn–Co–Mo nanosheet arrays are synthesized on nickel foam (NF) to form a three-dimensional (3D) network to take advantage of the electrical conductivity and viscosity of NF. Co3 O4 is produced directly in the 3D microchannels to achieve a large energy density and robust stability. In the test of the supercapacitor performance, the specific capacitance of Co3 O4 /Zn–Co–Mo/NF is 2169 F g −1 at a current density of 1 A g −1 . In addition, excellent long-term cycling stability is observed as manifested by specific capacitance retention of 85% after 4, 000 cycles at a current density of 25 A g −1 . As a catalyst in the hydrogen evolution reaction (HER), Co3 O4 /Zn–Co–Mo/NF shows an overpotential of 128 mV at 10 mA cm −2 . Our results confirm the dual functionality of the materials which have promising potential in energy storage and generation applications.